KETAKUTAN MENIKAH DALAM PERSPEKTIF FIKIH STUDI ATAS FENOMENA MARRIAGE IS SCARY - Hadi, Alfina (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2026)
The marriage is scary phenomenon has grown among young people, driven by family trauma, economic pressures, emotional instability, individualistic cultural influences, and unrealistic partner expectations. This study employs a qualitative, descriptive-analytical literature review using normative-theological and sociological approaches. The findings reveal that, from the perspective of Islamic jurisprudence, marriage is an act of worship with strategic wisdom, and its legal status is flexible depending on individual conditions. Rejection without valid shar‘i reasons contradicts the objectives of maqashid sharia. Proposed solutions include comprehensive premarital education, strengthening family roles, and applying contemporary ijtihad based on fiqh waqi’i and fiqh maqashidi. This study underscores the importance of integrating religious values and social strategies to build awareness of healthy marriages in accordance with Islamic principles